First Report of Nondeletional Hb H Disease Caused by an α2-Globin Gene Mutation: HBA2: c.184A>T. (4th May 2021) - Tian, Qi; Lei, Ya-Li; Xu, Li-Li; Li, Dong-Zhi
Abstract: We report a rare mutation, HBA2 : c.184A>T on the α2-globin gene, detected in a Chinese proband who presented with Hb H disease and a mild anemia. This frameshift mutation results in a premature termination of translation at position 61 of the α2-globin gene. Carriers of this mutation showed a borderline microcytic hypochromia. Our study indicates the importance of screening nondeletional α-thalassemia (α-thal) in areas with a particularly high prevalence of thalassemia such as in Southern China, especially for couples with one partner carrying an α 0 -thal deletion.